Alcohol and ischaemic heart disease in middle aged British men. Issue 6574 (21st March 1987) - Shaper, A G; Phillips, A N; Pocock, S J; Walker, M
Abstract : The relation between alcohol intake and ischaemic heart disease was examined in a large scale prospective study of middle aged men drawn from general practices in 24 British towns. After an average follow up of 6.2 years 335 of the 7729 men had experienced a myocardial infarction (fatal or non-fatal) or sudden cardiac death. No significant relation was found between reported alcohol intake and the incidence of such events. Though the group of light daily drinkers had the lowest incidence of ischaemic heart disease events, it also contained the lowest proportion of current smokers, had the lowest mean blood pressure, had the lowest mean body mass index, and contained the lowest proportion of manual workers. These characteristics are more likely to account for the apparent protective effect of alcohol against ischaemic heart disease than a direct effect of alcohol. Compared with the effects of established risk factors alcohol seems to be quite unimportant in the development of ischaemic heart disease.